Case for diagnosis - Lourenço de Azevedo Lima; Natacha de Carvalho Mello Haddad; Ricardo Barbosa Lima; Antonio Macedo D'Acri; Carlos José Martins (Sociedade Brasileira de Dermatologia, 2014)
Degos disease, also known as malignant atrophic papulosis, is a rare occlusive vasculopathy of unknown etiology characterized by infarcts in the dermis, gastrointestinal tract, central nervous system, and other organs. It is characterized by papules, which become umbilicated and evolve with a depressed porcelain-white central area, with an erythematous halo with telangiectasias. Histological findings include wedge-shaped dermoepidermal necrosis and blood vessel thrombosis. Approximately 50-60% of patients with systemic symptoms die within 2-3 years, most due to gastrointestinal perforation. We report a typical case, with lethal outcome, in a 45-year-old woman.